IMPLEMENTATION OF GREEN HUMAN RESOURCE MANAGEMENT PRACTICES FOR SUSTAINABLE ENVIRONMENTAL PERFORMANCE: MOTIVATION AND JOB SATISFACTION AMONG HOSPITAL EMPLOYEES IN BATAM - Evi Silvana Muchsinati; Tesalonika Sembiring; Adi Neka Fatyandi (Universitas Nusa Cendana, 2026)
This study investigates the relationship between green human resource management (Green HRM) practices, motivation, job satisfaction, and sustainable environmental performance in hospitals located in Batam. The study population comprises 200 employees from five hospitals in the city. Data were analyzed using SmartPLS 3 to assess the structural relationships among the variables. The findings demonstrate that all proposed hypotheses are statistically significant. Green HRM practices positively influence job satisfaction, employee motivation, and sustainable environmental performance. In addition, job satisfaction and motivation are found to effectively mediate the relationship between Green HRM practices and sustainable environmental performance. This indicates that environmentally oriented HR policies not only directly enhance environmental outcomes but also indirectly strengthen them by fostering positive employee attitudes and motivation. These results highlight the strategic importance of implementing Green HRM practices to support organizational sustainability objectives. The novelty of this research lies in identifying job satisfaction and motivation as critical mediating mechanisms that amplify the impact of Green HRM practices on achieving optimal environmental performance within healthcare institutions. Keywords: Green HRM Practices; Sustainable Environmental Performance; Motivation; Job Satisfaction